(The Effect of Acetate Anhhhydrida Ratio in the Process of Cellulose Acetylation of Pulp from Sengon (Paraserianthe falcataria) on the Production of Cellulose Triacetate Polymer) - Meurah Rosnelly, Cut; Aziz Darwis, Abdul; Noor, Erliza; -, Kaseno (Warta Industri Hasil Pertanian, 2010)
Almost all of Cellulose acetate is produced by reaction of cellulose and acetic anhydride using strong acids as catalyst and acetic acid as a solvent. A typical industrial process requires very high quality cellulose raw materials having a high a-cellulose content. The cellulose used as a raw material in this research is wood pulp of sengon (Paraserianthes falcataria) due to fast growing species and has potential used as a raw material as if has a high cellulose content. The main objective of this research was to obtain condition for making cellulose triacetate by applying applying ratio levels of acetic anhydride toward cellulose in acetylation process. Cellulose triacetate flake was produced by activation and acetylation process. Activation was carried out by mixing cellulose of sengon pulp with glacial acetic in proportionÂ  1:8 at 50oC about 15; 30; 60; 90, and 120 minutes. Acetylation is then conducted using reagents in following proportions relative to the pulp mass; variable of acetic anhydride ratio (3.35:1), (4:1), (5:1), and (6:1), acetic acid as solvent (4.5 : 1), sulfuric acid (0.015 : 1) as catalyst while controlling the reaction temperature at 50oC for 60 minutes. The result showed anhydride toward cellulose 3.35 in acetylation process.